The relationship of resilience and anxiety in volleyball - Patsiaouras, A.; Boziou, E.; Kontonasiou, D. (Scientific Journal of Sport and Performance, 2022)
The purpose of this study was to investigate the relationship between resilience levels and anxiety of volleyball players and to find possible differences that exist between the two genders. Participants included 195 volleyball players (37 male and 158 female), with the Self Evaluation Resilience test and the CSAI-2 test (Greek version) used as evaluation instruments. The data was analysed with SPSS 21.0 using Pearson`s r and t-test for independent samples. Results of Pearson`s r test showed positive intercorrelations between all the resilience variables and between resilience and self-confidence. The t-test showed statistically significant differences between male and female volleyball players in "forming relationships" and "self-efficacy" variables, with no other statistically significant differences observed for the rest of the resilience variables. Additionally, statistically significant differences were observed for "cognitive", "somatic" anxiety and "self-confidence" between the two genders of volleyball players. Future research should further investigate the relationship between resilience and self-confidence and how it affects the resilience level of volleyball players.